2014
DOI: 10.1111/tri.12485
|View full text |Cite
|
Sign up to set email alerts
|

An update on ABO-incompatible kidney transplantation

Abstract: SummaryABO-incompatible kidney transplantation is nowadays a well-established procedure to expand living donor transplantation to blood group incompatible donor/ recipient constellations. In the last two decades, transplantation protocols evolved to more specific isohaemagglutinin elimination techniques and established competent antirejection protection protocols without the need of splenectomy. ABOi kidney transplantation associated accommodation despite isohaemagglutinin reappearance, C4d positivity of perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 109 publications
(125 reference statements)
1
31
0
1
Order By: Relevance
“…In agreement with previous reports, C4d staining along peritubular capillary walls was found more often in the ABOi group compared to ABOc group of patients. However, this finding was not accompanied by histological findings of AMR [6,2224] . No other significant differences were found in histological parameters on kidney biopsies between ABOi and ABOc patients.…”
Section: Melexopoulou C Et Al Abo-incompatible Kidney Transplantationmentioning
confidence: 89%
“…In agreement with previous reports, C4d staining along peritubular capillary walls was found more often in the ABOi group compared to ABOc group of patients. However, this finding was not accompanied by histological findings of AMR [6,2224] . No other significant differences were found in histological parameters on kidney biopsies between ABOi and ABOc patients.…”
Section: Melexopoulou C Et Al Abo-incompatible Kidney Transplantationmentioning
confidence: 89%
“…As a result, it has become an acceptable treatment option in Japan, accounting for more than 30% of all living donor kidney transplantation. Excellent outcomes have been achieved, and the rates of graft survival in these patients are presently similar to those in recipients of ABO-compatible grafts [3][4][5][6][7]. Although our previous report demonstrated that this procedure may become a viable treatment option for elderly patients with ESKD [8], there have been few reports on elderly ABO-incompatible kidney transplantation.…”
mentioning
confidence: 93%
“…Nowadays, graft survival of ABOi KT recipients matches those of ABO-compatible (ABOc) KT recipients (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In cases that have low isohemagglutinin titers, ABOi KT can be performed with a reduced risk of acute AAMR and without the need for rituximab and apheresis (16 Hemagglutination is regarded as the preferable method to quantify isohemagglutinins, and s still commonly used (49). It is based on semi-quantitative measurement of blood-group-specific IgM (direct agglutination) or IgG (indirect detection using antiIgG reagents) (15,50). Alternative techniques used to detect anti-A/B antibodies include flow cytometry and surface plasmon resonance, which is a cell-independent method that enables detection-reagent-independent analysis of antibody-antigen binding using immobilized blood group A or B trisaccharides (6,51,52).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation